High-precision photometry by telescope defocusing - VII. The ultrashort period planet WASP-103 - Southworth, John; Mancini, Luigi; Ciceri, Simona; Budaj, J.; Dominik, M.; Figuera Jaimes, R.; Haugbølle, T.; Jørgensen, U. G.; Popovas, A.; Rabus, M.; Rahvar, S.; von Essen, C.; et al. (Monthly notices of the Royal Astronomical Society, 2015)
Abstract. We present 17 transit light curves of the ultrashort period planetary system WASP-103, a strong candidate for the detection of tidally-induced orbita
Published: 17 December 2014
Gesehen am 19.06.2020